Clinical, neuroimaging and neuropathological features of a new chromosome 9p-linked FTD-ALS family. Issue 2 (20th June 2010) - Boxer, Adam L; Mackenzie, Ian R; Boeve, Bradley F; Baker, Matthew; Seeley, William W; Crook, Richard; Feldman, Howard; Hsiung, Ging-Yuek R; Rutherford, Nicola; Laluz, Victor; Whitwell, Jennifer; Foti, Dean; et al.
Abstract : Background: Frontotemporal dementia-amyotrophic lateral sclerosis (FTD-ALS) is a heritable form of FTD, but the gene(s) responsible for the majority of autosomal dominant FTD-ALS cases have yet to be found. Previous studies have identified a region on chromosome 9p that is associated with FTD and ALS. Methods: The authors report the clinical, volumetric MRI, neuropathological and genetic features of a new chromosome 9p-linked FTD-ALS family, VSM-20. Results: Ten members of family VSM-20 displayed heterogeneous clinical phenotypes of isolated behavioural-variant FTD (bvFTD), ALS or a combination of the two. Parkinsonism was common, with one individual presenting with a corticobasal syndrome. Analysis of structural MRI scans from five affected family members revealed grey- and white-matter loss that was most prominent in the frontal lobes, with mild parietal and occipital lobe atrophy, but less temporal lobe atrophy than in 10 severity-matched sporadic bvFTD cases. Autopsy in three family members showed a consistent and unique subtype of FTLD-TDP pathology. Genome-wide linkage analysis conclusively linked family VSM-20 to a 28.3 cM region between D9S1808 and D9S251 on chromosome 9p, reducing the published minimal linked region to a 3.7 Mb interval. Genomic sequencing and expression analysis failed to identify mutations in the 10 known and predicted genes within this candidate region, suggesting that next-generation sequencing may be needed to determine the mutational mechanism associated with chromosome 9p-linked FTD-ALS. Conclusions: Family VSM-20 significantly reduces the region linked to FTD-ALS on chromosome 9p. A distinct pattern of brain atrophy and neuropathological findings may help to identify other families with FTD-ALS caused by this genetic abnormality.